Serum neutralization of feline immunodeficiency virus is markedly dependent on passage history of the virus and host system. - Baldinotti, F (1994)
Sera from feline immunodeficiency virus (FIV)-infected cats exhibited extremely low levels of neutralizing antibodies against virus passaged a few times in vitro (low passage), when residual infectivity was assayed in the CD3+ CD4- CD8- MBM lymphoid cell line or mitogen-activated peripheral blood mononuclear cells. By sharp contrast, elevated titers of highly efficient neutralizing activity against FIV were measured, by use of high-passage virus, in assays on either the fibroblastoid CrFK or MBM cell line. However, high-passage virus behaved the same as low-passage virus after one in vivo passage in a specific-pathogen-free cat and reisolation. Subneutralizing concentrations of infected cat sera enhanced the production of low-passage virus by MBM cells, an effect not seen with high-passage virus in CrFK cells. These qualitative and quantitative discrepancies could not be attributed to differences in the amount of immunoreactive viral material, to the amount of infectious virus present in the viral stocks, or to the presence of anti-cell antibodies. The observed effects were most likely due to the different passage history of the viral preparations used. The observation that neutralizing antibodies detected with high-passage virus were broadly cross-reactive in assays with CrFK cells but isolate specific in MBM cells suggests also that the cell substrate can influence the result of FIV neutralization assays. This possibility could not be tested directly because FIV adapted to grow in CrFK cells had little infectivity for lymphoid cells and vice versa. In vitro exposure to infected cat sera had little or no effect on the ability of in vivo-passaged FIV to infect cats. These data reveal no obvious relationship between titers against high-passage virus and ability to block infectivity of FIV in cats and suggest caution in the use of such assays to measure vaccine efficacy. In conclusion, by contrast with what has been previously reported for the use of CrFK cells and high-passage virus, both natural and experimental infections of cats with FIV generate poor neutralizing antibody responses with regard to in vivo protection.